Study of the relationship between mineralogical types and potential radon in rocks of the region of Serra do Gandarela – Quadrilátero Ferrífero-MG. (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The Quadrilátero Ferrífero (QF) is one of the most well-known metallogenetic provinces in the world and has its geological context well studied since the end of the 17th century. The Serra do Gandarela is positioned in the northeast of the QF and is supported by units of the Minas Supergroup. The Moeda Formation (MF) in the Serra do Gandarela hosts an uranium (U) occurrence which was recently characterized in terms of mineralogical context. Uraninite, coffinite and brannerite are the main U minerals present. It is expected that mineralogy and lithology contribute to radon emanation and exhalation, the radon (Rn) transport from the soil to the atmosphere. In this work, the Rn exhalation was correlated to the lithological types. Samples from the MF conglomerates and Nova Lima group schists were collected from the Serra do Gandarela. Rn exhalation measurements were performed on the samples with AlphaGUARD detector. These values were compared to the U content of samples obtained via INAA. The result of INAA was more expressive in the MF conglomerate sample from the NUCLEBRÁS drillcore, with a U concentration value of 24 µg.g-1. The sample that had the highest average exhalation rate was also the same. The lowest value presented for both U concentration and average exhalation rate was shale, which were, 2 µg.g-1 and 180 Bq.m-3, respectively. The results are relevant for exploration and mining activities, during which Rn can accumulate in galleries. Additionally, the knowledge of the characteristic emanometric can be an important tool for geological and environmental studies.